Proceedings From the Sixth Annual IEEE Systems, Man and Cybernetics (SMC) Information Assurance Workshop, 2005.
DOI: 10.1109/iaw.2005.1495939
|View full text |Cite
|
Sign up to set email alerts
|

A visualization paradigm for network intrusion detection

Abstract: A b s h c tinformation and minimize any mental transformations that w e present a novel Paradigm for visual correlation of network alerts from disparate logs. This paradigm facilitates and promotes situational awareness in complex network enmust be applied to the data. O u r goal is t o enable the users to quickly decide how pervasive and how severe problems vironments. Our approach is based on the notion that, by definition, a n alert must posses three attributes, namely: What, When, and Where. This fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 10 publications
1
47
0
3
Order By: Relevance
“…Rigorous scientific testing has demonstrated that dwelling in such data representation architectures allows people (i.e., network managers, traders, anesthesiologists, etc.) to make more accurate, faster, and better decisions than with existing systems [26,37,30,[42][43][44][53][54][55][56][57][58]. And they can do so while with reducing their cognitive load, stress, and training time.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous scientific testing has demonstrated that dwelling in such data representation architectures allows people (i.e., network managers, traders, anesthesiologists, etc.) to make more accurate, faster, and better decisions than with existing systems [26,37,30,[42][43][44][53][54][55][56][57][58]. And they can do so while with reducing their cognitive load, stress, and training time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a longer periodicity could lead to a frame that does not have much connection to the frame displayed before the last refresh. The periodicity should be defined such that there is a balance the two issues, so that the frame of data that appears after the last refresh is not vastly different from the frame just before the refresh [6].…”
Section: ) Visualization Techniquementioning
confidence: 99%
“…Certain elements of the data are of key importance to the operator at this stage: event severity, target and time, or "the W3 of What, Where, When" [11]. These represent the minimum dimensionality that can be known in order to start building an actionable model of the situation (the date, time, IP and priority fields in the IDS alert logs).…”
Section: ) Monitoringmentioning
confidence: 99%